Expression of PD-L1 and PD-1 in stage T4 rectal cancer tissues and surrounding metastatic lymph nodes and correlation with prognosis: PD-L1 and PD-1 in rectal cancer tissues - Wang, Yu; Lu, Haofeng; Li, Mi (Cellular and Molecular Biology, 2022)
The expressions of programmed death ligand 1 (PD-L1) and programmed death receptor 1 (PD-1) in T4 rectal cancer tissues and surrounding metastatic lymph nodes were analyzed and correlated with prognosis. For this purpose, ninety-eight patients with T4 rectal cancer treated in our hospital from July 2021 to July 2022 were selected, and surgically resected rectal cancer tissues as well as para carcinoma tissue samples, and surrounding metastatic lymph node tissues were obtained from all patients. Analysis of PD-L1 and PD-1 expression in rectal cancer tissues as well as in adjacent tissue specimens and surrounding metastatic lymph node tissues were performed using immunohistochemical staining. PD-L1 and PD-1 expression were analyzed in relation to lymph node metastasis, maximum tumor diameter, as well as histological analysis, and the relationship between the two and prognosis was analyzed. Immunohistochemistry for PD-L1, PD-1 revealed that both proteins were expressed in association with the target cytoplasm as well as within the cell membrane; The number of cases with positive expression of PD-L1 and PD-1 in cancer tissues was significantly higher than the number of cases with expression in adjacent tissues, which was statistically significant (P < 0.05); The expression rates of PD-L1, PD-1 in poor expression in progression-free survival as well as in progression survival were significantly higher than those in medium and high expression with statistical significance (P < 0.05); Compared with patients without lymph node metastasis, patients with T4 rectal cancer with lymph node metastasis had a higher number of cases with high expression levels of PD-L1 and PD-1 proteins, and the difference was statistically significant (P < 0.05); PD-L1 and PD-1 in T4 stage rectal cancer prognosis is closely related, distant metastasis as well as lymph node metastasis has a greater effect on PD-L1 and PD-1. PD-L1 and PD-1 showed abnormal expression in T4 rectal cancer tissues as well as in surrounding metastatic lymph nodes, and PD-L1 and PD-1 were closely related to prognosis in T4 rectal cancer, distant metastasis, as well as lymph node metastasis had a greater effect on PD-L1 and PD-1. Its detection is able to provide a certain data reference for the prognosis of T4 rectal cancer.